Using telemedicine and wearable technology to establish a virtual clinic for people with Parkinson’s disease - Lauren Evans; Biju Mohamed; Edward Christopher Thomas (BMJ Open Quality)
Background To develop an effective, patient-centred and sustainable service, we set up a virtual clinic (VC) for patients with Parkinson’s disease, combining phone consultations and reports from wearable technology. The Parkinson’s Kinetigraph (PKG) is a wrist-worn device providing objective motor assessment, generating a report used by clinicians to optimise medication regimens.Interventions A pilot study of VC was designed using quality improvement methodology. For a VC appointment, patients were phoned by a clinician. After discussing symptoms and reviewing the PKG report, the clinician could decide on any medication changes or other interventions and relay this to the patient’s general practitioner in a clinic letter. Patient feedback was gathered via questionnaires and data collected on the outcomes and timings of the consultations.Results Over 12 clinics, 61 patients had VC appointments. Of questionnaire respondents, 89% were satisfied with VC (n=41). At VC, the clinician was able to make a treatment decision comparable to a face-to-face clinic in 79% of cases (n=48). Reasons appointments were deemed unsuccessful included issues with the PKG, speech or hearing problems and complex phase of disease. VC appointments, including administration time, last on average 22 min. This compares to 20 min face-to-face appointments but these do not include administration time.Conclusions We have demonstrated a safe and effective VC template. Most VC appointments are equivalent to face-to-face clinic in terms of treatment outcome. Success could be further improved by appropriate patient selection. Using VC is time saving and can result in releasing face-to-face appointment slots for those in urgent need or newly referred patients. Further cost analysis is required; the cost of the PKG alone is more expensive than a face-to-face appointment, but this does not take into account other value added, such as patient convenience and satisfaction, and reduced need for ambulance transport.